2010
DOI: 10.3109/10717544.2010.522612
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoevaluation of ketotifen fumarate-loaded silicone hydrogel contact lenses for ocular drug delivery

Abstract: The purpose of this work was to evaluate the usefulness of silicone hydrogel contact lenses loaded with ketotifen fumarate for ocular drug delivery. First, silicone contact lenses were prepared by photopolymerization of bitelechelic methacrylated polydimethylsiloxanes macromonomer, 3-methacryloxypropyltris(trimethylsiloxy)silane, and N,N-dimethylacrylamide using ethylene glycol dimethacrylate as a cross-linker and Darocur 1173 as an initiator followed by surface plasma treatment. Then, the silicone hydrogel ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…The authors observed no signs of discomfort in the animal models, though some of the eyes did develop corneal neovascularisation, which was possibly due to poor fitting lenses. In an earlier work, Xu et al also used rabbits to demonstrate in vivo release behaviour and for one of their contact lenses, observed no irritation or protein deposition [19]. The authors did, however, observe some lens deposition on another of their materials, again demonstrating the need for in vivo studies.…”
Section: Introductionmentioning
confidence: 91%
“…The authors observed no signs of discomfort in the animal models, though some of the eyes did develop corneal neovascularisation, which was possibly due to poor fitting lenses. In an earlier work, Xu et al also used rabbits to demonstrate in vivo release behaviour and for one of their contact lenses, observed no irritation or protein deposition [19]. The authors did, however, observe some lens deposition on another of their materials, again demonstrating the need for in vivo studies.…”
Section: Introductionmentioning
confidence: 91%
“…1 The prevailing model of the pathogenesis of allergic conjunctivitis is sensitization of the ocular surface to specific antigens, such as pollen or dust, leading to proliferation of antigen-specific mast cells and the production of immunoglobulin E. 3 Upon subsequent exposure, the antigen binds to and triggers the cross-linking of a pair of immunoglobulin E antibodies located on the surface of conjunctival mast cells, ultimately causing the release of stored chemical messengers such as histamine, tryptase, leukotrienes, prostaglandins, cytokines, and platelet activating factor, all of which contribute to the signs and symptoms that characterize allergic conjunctivitis, including redness, swelling, and edema. [3][4][5] Ketotifen fumarate (KF) is a benzocycloheptathiophene derivative that is widely known to alleviate the signs and symptoms of SAC through multiple pharmacological actions. 4 It is a relatively small molecule, with the molecular weight (MW) of the ion being only 309.4 g/mol.…”
mentioning
confidence: 99%
“…7 Several novel drug delivery systems (DDSs) aimed at addressing the issue of adherence and ensuring consistent IOP reduction are under development. Various systems have been proposed, including contact lenses, [8][9][10][11] ocular inserts, 12,13 and injectable biodegradable micro-and nanoparticles. [14][15][16][17] The emergence of nanomaterials and nanometerorder devices that are applicable to ophthalmology is highly awaited.…”
mentioning
confidence: 99%